Dominance of in situ produced particulate organic carbon in a subtropical reservoir inferred from carbon stable isotopes - Bueno, Carolina de Castro [UNESP]; Frascareli, Daniele [UNESP]; Gontijo, Erik S. J. [UNESP]; van Geldern, Robert; Rosa, André H. [UNESP]; Friese, Kurt; Barth, Johannes A. C. (Springer Nature, 2020)
Sources of particulate organic carbon (POC) play important roles in aqueous carbon cycling because internal production can provide labile material that can easily be turned into CO2. On the other hand, more recalcitrant external POC inputs can cause increased loads to sedimentary organic matter that may ultimately cause CH4 release. In order to differentiate sources, stable isotopes offer a useful tool. We present a study on the Itupararanga Reservoir (Brazil) where origins of POC were explored by comparing its isotope ratios (δ13CPOC) to those of dissolved inorganic carbon (δ13CDIC). The δ13CPOC averaged around − 25.1‰ in near-surface waters, which indicates higher primary production inferred from a fractionation model that takes into account carbon transfer with a combined evaluation of δ13CPOC, δ13CDIC and aqueous CO2. However, δ13CPOC values for water depths from 3 to 15 m decreased to − 35.6‰ and indicated different carbon sources. Accordingly, the δ13CDIC values of the reservoir averaged around + 0.6‰ in the top 3 m of the water column. This indicates CO2 degassing and photosynthesis. Below this depth, DIC isotope values of as low as − 10.1‰ showed stronger influences of respiration. A fractionation model with both isotope parameters revealed that 24% of the POC in the reservoir originated from detritus outside the reservoir and 76% of it was produced internally by aqueous CO2 fixation.